Progress in treatment of neuromyelitis optica spectrum disorders (NMOSD): Novel insights into therapeutic possibilities in NMOSD. (15th April 2022) - Shi, Mingchao; Chu, Fengna; Jin, Tao; Zhu, Jie
Abstract: Neuromyelitis optica spectrum disorder (NMOSD) is a rare autoimmune inflammatory demyelinating disorder of the central nervous system (CNS), which is a severely disabling disorder leading to devastating sequelae or even death. Repeated acute attacks and the presence of aquaporin‐4 immunoglobulin G (AQP4‐IgG) antibody are the typical characteristics of NMOSD. Recently, the phase III trials of the newly developed biologicals therapies have shown their effectiveness and good tolerance to a certain extent when compared with the traditional therapy with the first‐ and second‐line drugs. However, there is still a lack of large sample, double‐blind, randomized, clinical studies to confirm their efficacy, safety, and tolerability. Especially, these drugs have no clear effect on NMOSD patients without AQP4‐IgG and refractory patients. Therefore, it is of strong demand to further conduct large sample, double‐blind, randomized, clinical trials, and novel therapeutic possibilities in NMOSD are discussed briefly here. Abstract : Several drugs with different mechanisms and targets have been applied in clinic for therapy of NMOSD patients, included first‐line, second‐line, and new biologicals therapies. Other novel insights into therapeutic possibilities in NMOSD include targeting Th17 cells and blocking IL23/IL17/Th17 pathway and stem cell therapies, etc.